Pengaruh Return on Asset (ROA), Total Aset Turnover (TATO) dan Debt to Equity Ratio (DER) Terhadap Price to Book Value (PBV) pada Perusahaan Subsektor Produk Perawatan Tubuh yang Terdaftar di Bursa Efek Indonesia (BEI) - Sakti, Gunawan; Nurulrahmatia, Nafisah; Munandar, Aris (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER) on Price to Book Value (PBV) in personal care products subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with an associative method. The study population consists of 11 companies, while the sample was determined using a purposive sampling technique, resulting in 6 companies with 30 observations. The data used are secondary data from annual financial reports and were analyzed using multiple linear regression with the help of SPSS version 26. The results show that partially ROA and DER have no significant effect on PBV, while TATO has a positive and significant effect on PBV. Simultaneously, ROA, TATO, and DER have a significant effect on PBV with a coefficient of determination of 57.8%. This finding indicates that asset utilization efficiency is a more determining factor in increasing company value in the research model than profitability and capital structure individually. Thus, a company's ability to optimize assets to generate sales is a strategic aspect in enhancing market perception of the company's value. The results of this study imply that companies in the personal care products subsector need to prioritize effective asset management as part of their value-enhancing strategy.